Analyse du comportement dynamique des roues de turbomachines immergees - Jacquet-Richarde, Georges; Dal-Ferro, Christian (European Journal of Computational Mechanics, 1995)
A method, adapted to the prediction of the dynamic behaviour of immersed turbomachinery wheels, is proposed. The method allows efficient computation of natural frequencies, mode shapes and hannonic response of the coupled fluid s.tructure system. The fluid is supposed incompressible and at rest. The size of the problem is appreciably reduced using the properties of wave propagation in periodic systems combined with modal techniques applied to both structure and fluid domains. This procedure allows the computation of industrial structures on standard computer workstations, without noticeable loss of accuracy. The method is applied to an immersed centrifugal pump wheel. The numerical results obtained are compared to experimental results.